Time-frequency analysis of geopolitical risk and food commodity market: a wavelet based investigation - Aiswarya S; Muthumeenakshi Muralikrishna (Agricultural and Resource Economics)
Purpose. The most recent conflicts have demonstrated that geopolitical risk has evolved into a significant issue that has an impact on the global food markets. Through the use of bi-wavelet coherence analysis, the study aimed to establish the ways in which geopolitical risk and climate policy uncertainties influences the food commodity market using Geopolitical Risk Index (GPR index), Climate Policy Uncertainty Index (CPU index) and the five components that make up the FAO Food Price Index (FPI).